Utility of the urine reagent strip leucocyte esterase assay for the diagnosis of meningitis in resource‐limited settings: meta‐analysis. Issue 9 (10th July 2017) - Bortcosh, William; Siedner, Mark; Carroll, Ryan W.
Abstract: Objective: Diagnosis of bacterial meningitis often requires cytometry, chemistry and/or microbiologic culture capabilities. Unfortunately, laboratory resources in low‐resource settings (LRS) often lack the capacity to perform these studies. We sought to determine whether the presence of white blood cells in CSF detected by commercially available urine reagent strips could aid in the diagnosis of bacterial meningitis. Methods: We searched PubMed for studies published between 1980 and 2016 that investigated the use of urine reagent strips to identify cerebrospinal fluid (CSF) pleocytosis. We assessed studies in any language that enrolled subjects who underwent lumbar puncture and had cerebrospinal fluid testing by both standard laboratory assays and urine reagent strips. We abstracted true‐positive, false‐negative, false‐positive and true‐negative counts for each study using a diagnostic threshold of ≥10 white blood cells per microlitre for suspected bacterial meningitis and performed mixed regression modelling with random effects to estimate pooled diagnostic accuracy across studies. Results: Our search returned 13 studies including 2235 participants. Urine reagent strips detected CSF pleocytosis with a pooled sensitivity of 92% (95% CI: 84–96), a pooled specificity of 98% (95% CI: 94–99) and a negative predictive value of 99% when the bacterial meningitis prevalence is 10%. Conclusions: Urine reagent strips could provide a rapid and accurate tool to detect CSF pleocytosis, which, if negative, can be used to exclude diagnosis of bacterial meningitis in settings without laboratory infrastructure. Further investigation of the diagnostic value of using protein, glucose and bacteria components of these strips is warranted.